2020
DOI: 10.1186/s12879-020-05520-7
|View full text |Cite
|
Sign up to set email alerts
|

Who fails to return within 30 days after being tested positive for HIV/STI in a free testing centre?

Abstract: Background Some patients who test positive for sexually transmitted infections (STIs) fail to return for results and treatment. To target improvement actions, we need to find out who these patients are. This study aimed to explore factors associated with failure to return within 30 days (FTR30) after testing among patients with positive results in a free STI testing centre in Paris. Methods All patients with at least one positive result between October 2016 and May 2017 and who completed a self-administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Previous studies have not found any demographic factors significantly associated with likelihood of STI treatment completion. 5 , 9 While a retrospective review is unable to determine the reasons for loss to follow-up (LTFU), these findings may reflect greater awareness and less stigma around STIs among younger 10 or non-heterosexual 11 patients, and private insurance may represent a proxy for patients who have the financial means to return for treatment or maintain a telephone for result notification.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not found any demographic factors significantly associated with likelihood of STI treatment completion. 5 , 9 While a retrospective review is unable to determine the reasons for loss to follow-up (LTFU), these findings may reflect greater awareness and less stigma around STIs among younger 10 or non-heterosexual 11 patients, and private insurance may represent a proxy for patients who have the financial means to return for treatment or maintain a telephone for result notification.…”
Section: Discussionmentioning
confidence: 99%
“…Markers of material and social privilege, such as completing higher education, and phylogenetic clustering between people living with HCV/HIV co‐infection suggest the need to tailor HCV prevention messaging in Australia to very specific population demographic groups. Further, people with lower levels of education may have lower levels of health literacy, 52 resulting in fewer of them presenting to services to get tested or treated, 53 and being underrepresented in studies such as this. This may result in phylogenetic clustering being skewed towards people with higher levels of education due to them presenting to services more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…specific population demographic groups. Further, people with lower levels of education may have lower levels of health literacy,52 resulting in fewer of them presenting to services to get tested or treated,53 and being underrepresented in studies such as this. This may result in phylogenetic clustering being skewed towards people with higher levels of education due to them presenting to services more frequently.…”
mentioning
confidence: 99%
“…Studies among MSM in other countries found that 5–11% of MSM had failure-to-return for HIV test results [ 19 , 22 ]. Prior literature reveals significant correlates of failure-to-return for HIV test results, including perceived risk of HIV infection, inconsistent condom use, and certain demographic characteristics such as male gender, young age, unemployment, rural residence, and low educational attainment [ 19 , 23 , 24 , 25 , 26 ]. Although these studies provide salient insights into factors associated with failure-to-return for HIV test results, few studies assessed relevant psychosocial determinants and their effects on HIV prevention uptake.…”
Section: Introductionmentioning
confidence: 99%